The impact of selected factors on early diagnosis of multiple primary cancers in patients with uveal melanoma - Mierzwa-Dobranowska, Marzena; Romanowska-Dixon, Bożena (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To find differences between a group of patients with intraocular melanoma and another primary cancer and a group of patients with no identifiable second primary cancer. Material and methods: The analysis involved 240 participants, selected from patients who were treated for uveal melanoma at the Department of Ophthalmology and Ocular Oncology of the Jagiellonian University Medical College between the year 1998 and 2007. Among those patients 97 were diagnosed with one or more independent primary cancers. Those patients were subject to a comparative analysis with a second group of 143 patients who had uveal melanoma with no identifiable second primary cancer. Results: Statistically significant differences between the group of patients with intraocular melanoma and another primary cancer, and the group of patients with uveal melanoma (but without another diagnosed primary neoplasm) were as follows: more common family history of cancer, better education, living in cities (especially with a population over 500 thousand), previous surgery except for uveal melanoma, and two or less than two pregnancies in the case of women. Conclusions : This analysis revealed that more common family history of cancer, better education, living in cities (especially with a population over 500 thousand), previous surgery, except for uveal melanoma, and two or less than two pregnancies in the case of women, were associated with a higher rate of detection of multiple primary cancers.